2013
DOI: 10.1002/pssr.201307057
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic and magnetic properties of quaternary half‐metallic Heusler alloy CoFeCrAl

Abstract: We have investigated the structural, electronic and magnetic properties in quaternary CoFeCrAl Heusler alloy. Rietveld refinement and Mössbauer spectroscopy of samples quenched from 973 K show absence of the A2 phase and presence of a highly ordered B2‐type structure. Full‐potential linearized augmented plane wave calculations using the experimental lattice constant show that there is an energy gap of 0.41 eV around the Fermi level in the bands for minority spin electrons. Partial substitution of Co by Fe in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 22 publications
3
17
1
Order By: Relevance
“…The XRD results of Bainsla et al are found to be in good agreement with the reports by Luo et al [47] and Nehra et al [48].…”
Section: B Cofecrz (Z = Al and Ga) Alloyssupporting
confidence: 86%
See 2 more Smart Citations
“…The XRD results of Bainsla et al are found to be in good agreement with the reports by Luo et al [47] and Nehra et al [48].…”
Section: B Cofecrz (Z = Al and Ga) Alloyssupporting
confidence: 86%
“…Curie temperature of 460 K for the alloy was obtained using the thermomagnetic curves recorded by them. Nehra et al [48] also studied the magnetic properties of the as-melted as well as quenched CoFeCrAl alloy and found a bifurcation between the zero field cooled and field 13 cooled thermomagnetic data. They also observed that the difference between these two data decreases with increase in the cooling field and entirely disappears in a cooling field of ~1.5…”
Section: B Cofecrz (Z = Al and Ga) Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical calculations have shown that anti-site disorder destroys the high spin polarization [12] by disturbing the Fermi surface at the top of spin-down sub-band. Attempts have been made to adjust the position of the Fermi level in various Heusler alloys by partial substitution of transition metal occupying the Y site by another transition metal for example Co 2 Mn 1Àx Fe x Si [13] and Co 2 Cr 1Àx Fe x Al [14]. However, the theoretically predicted values of spin polarization values were not achieved.…”
Section: Introductionmentioning
confidence: 93%
“…In such Heusler alloys, one of the X atoms is completely substituted by another transition metal element. There are only few examples known for such quaternary alloys, CoFeMnZ (Z ¼Al, Ga, Si and Ge) [20,21], CoFeCrAl [22], CoFeMnSi [23] NiCoMnZ (Z ¼Al, Ge and Sn) [24] NiFeMnGa, NiCoMnGa and CuCoMnGa [25] CoFe 1 þ x Ti 1 À x Al and CoMn 1 þ x V 1 À x Al [26,27]. Ordered quaternary Heusler alloys are formed when the occupancy of each atom at the four Wyckoff positions is unity.…”
Section: Introductionmentioning
confidence: 98%